How does environmental perception affect the willingness of university students to return home to start a business? - Rongkun Qi; Dajiang Wang; Yuqing Yang; Feixia Wu (Cogent Business & Management, 2023)
Entrepreneurial intentions play a crucial role in predicting entrepreneurial behavior. Entrepreneurship is not a solitary individual endeavor, but rather, it is interconnected with the interplay between the individual and society. Previous studies have not clearly distinguished the unique role of entrepreneurs as individuals engaging in the entrepreneurial process, and there remains a lack of research on the psychological processes of entrepreneurs' interactions with other people and their surroundings, which leaves a gap to be filled in entrepreneurship research. Therefore, this study introduces the concept of entrepreneurial environment cognition and re-examines the "process of interaction between entrepreneurial environment and subjects." When university students return to their hometown to start a business, the entrepreneurial mindset and perspective towards the entrepreneurial environment in their hometown can significantly impact their entrepreneurial intentions. This study, based on data from 302 respondents, integrates insights from entrepreneurship and cognitive psychology research to illustrate the influence of entrepreneurship and cognitive psychology in the process of university students returning to their hometown to start a business. To ensure construct validity and reliability, Cronbach's alpha, Composite Reliability, and heterotrait-monotrait ratio tests are adopted. Additionally, this study further explains the mechanisms underlying this relationship by outlining the role of entrepreneurial passion and policy support. The findings suggest that environmental perceptions contribute to the willingness of university students to return to their home town for entrepreneurship, while entrepreneurial passion acts as a bridge and presents a partially mediating role in the relationship. In addition, it was found that the pathway environmental perceptions-willingness to return to their home town for entrepreneurship was more significantly moderated by policy support. These findings also provide reference and suggestions for the government and other decision-making departments.
Keywords: 650; College student; entrepreneurial passion; environmental perception; intention to return to the hometown and start a business; policy support